Adsorption and controlled release of three kinds of flavors on UiO‐66. Issue 4 (24th February 2020) - Mao, Deshou; Xie, Congjia; Li, Zhiyu; Hong, Liu; Qu, Rongfen; Gao, You; He, Jiao; Wang, Jiaqiang
Abstract: Delivery systems for controlled release of fragrances are significantly essential in the flavor and fragrance industry due to a limited life span (premature evaporation and degradation) of fragrance compounds. Recently, several adsorption materials such as porous materials have been developed in delivery systems for targeted fragrance release. In this work, UiO‐66, a member of metal–organic framework (MOF) family with high porosity and greater adsorbability, was selected as a prospective alternative to traditional porous adsorbents for controlled release of fragrances. Isophorone, eugenol, and β‐ionone with strong aroma are widely used as perfume flavors, soap flavor, cosmetic flavors, and even as a food‐flavoring agents, and were chosen as representative fragrances for adsorption and controlled release studies. The adsorption and release behavior of fragrances on UiO‐66 was evaluated by high‐performance liquid chromatography (HPLC). The UiO‐66 with high surface area (1, 076 m 2 /g) achieved effective storage and controlled release for isophorone, eugenol, and β‐ionone. The adsorption rates of isophorone, eugenol, and β‐ionone can reach 99.4%, 99.9%, and 60.2%, respectively. Additionally, the release of these fragrances from UiO‐66 can sustain over 20 days. UiO‐66 exhibited higher release rate over eugenol with desorption rates of 95.2% than that of β‐ionone (52.6%) and isophorone (49.6%), respectively, suggesting a good adsorption‐release selectivity of UiO‐66 to different fragrances. This study further confirms the usability of UiO‐66 in fragrance release and extends the application of MOF porosity in aroma release. Abstract : The micropore‐dominated Zr‐based metal framework (UiO‐66) with high surface area (1, 076 m 2 /g) exhibits excellent adsorption capacity (60.2%~99.9% of adsorption rate) and effective controlled release (49.6%~95.0% release rate) over 20 days toward common flavors (isophorone, eugenol, and β‐ionone), which can be considered as a novel prospective porous material for controlled release of fragrances due to more advantages than traditional porous materials. The adsorption and diffusion mechanism of flavor substances on UiO‐66 was revealed.